Serious gaming for digital growth. Reducing waste through the Lean mindset - Maria Antonietta Esposito; Filippo Bosi; Caterina Ferraro (Agathón)
The Italian context’s push towards BIM should be considered an opportunity to implement a digital transition towards the use of IT tools, through a culturally innovative approach to construction provided by Lean thinking and its gamification. The Lean approach leverages proven strategies to increase the quality of the production process. However, its application is still difficult: hence the need to convey effective proposals that use the structure of games to present actual ‘simulations’ of the production process. This paper aims to highlight how the gamified application of Lean processes constitutes a transformative formula enabling digitalisation, to achieve sustainability goals in the AECO Industry through original training approaches.